VISUAL COMMUNICATION STRATEGY IN ATTRACTING CONSUMER ATTENTION THROUGH CULINARY PACKAGE PROMOTION: A CASE STUDY OF MARUGAME UDON - Surya Pranata; I Made Budiasa; I Putu Adi Saskara (JKKB: Jurnal Kajian Komunikasi Budaya (JCCS: Journal of Cultural Communication Studies), 2025)
The culinary industry is experiencing rapid transformation characterized by changing consumption behaviors, heightened market competition, and the growing significance of creative marketing communication. Visual communication plays a strategic role in constructing brand identity and influencing consumer perception, particularly within fast-food restaurant marketing. This study examines the visual communication strategies applied by Marugame Udon in promoting culinary packages and evaluates their effectiveness in attracting consumer attention and shaping brand perception. Employing a qualitative case study approach, data were collected through observation, visual documentation, and in-depth interviews with consumers, marketing personnel, and design teams. The analysis draws on Stuart Hall’s Representation Theory, the AIDA model, and visual perception theory to interpret how visual messages are constructed and decoded. The results reveal that the integration of interior aesthetics, service presentation, and promotional visuals forms a consistent and persuasive communication strategy. Elements such as warm color tones, legible typography, Japanese-themed ornaments, and appetizing food imagery enhance authenticity, emotional engagement, and consumer loyalty.